Analisis Pengaruh Strategi Adaptasi Terhadap Kinerja UMKM Di Kabupaten Mamuju - Hari Yeni; J.Fuji Inzani SL (AkMen JURNAL ILMIAH, 2021)
The Covid-19 outbreak has brought changes to every line of life, including the activities of Micro, Small and Medium Enterprises (MSMEs). MSME actors are expected to be able to adapt to changes that occur to minimize the continued impact of the pandemic, such as termination of employment or business closures. The MSME actor adaption need to be carried out systematically and strategically so they do not have problems when facing similar conditions and as part of a long-term business pattern. Therefore, this study aimed to determine the effect of adaptation strategies on the performance of SMEs, product adaptation and marketing. The research method was used quantitative methods to apply multiple linear regression models to test the proposed hypothesis by first ensuring that the data collected has met the validity, reliability, and classical assumptions. The results showed that the product and marketing adaptation strategy had a partial (tcount > ttable; p < 0.05) and simultaneous (Fcount > Ftable; p < 0.05) performance on the performance of MSMEs in Mamuju Regency where the dominant factor influencing was the marketing adaptation strategy. Based on these results, it can be suggested to MSME actors to adapt marketing by utilizing various available marketing channels in order to be able to improve performance and adapt products based on market response